THE RELATIONSHIP BETWEEN ORAL HEALTH AND CARDIOVASCULAR DISEASE AND DIABETES - Abdullah Saleh Abdullah Alamri, Abdulrahman Khalid Ghayib Alghubaywi, Ahmed Abdullah Husain Alnawdali, Suliman Abdullah Saleh Algazlan, Emad Saud S Almutairi, Nourah Mohammed Aldosariy, Mohammed Ahmed Asiri,; Abdullah Muhammad Omar Alotain, Ashwaq Fahad Bader Alotaibi, Ibtisam Abdullah Lafi Alharbi, Abdullah Hamed Aljowayed, Bandar Madshar Mansor Alanazi, Shaima Ali Mohammed Alhazemi (Chelonian Research Foundation, 2022)
Periodontitis is a persistent inflammatory condition caused by the presence of a bacterial biofilm known as dental plaque. It affects the periodontal ligaments and the bone that surrounds the teeth. Over the last several decades, many lines of data have substantiated the correlation between periodontitis and overall health. Periodontitis, a chronic inflammatory condition, has similarities with cardiovascular disease (CVD) and diabetes. Multiple studies have shown a two-way connection between periodontal health and these diseases. Individuals with diabetes have a higher vulnerability to infections and a greater likelihood of developing periodontitis compared to those without this condition. Similarly, it is now clear that periodontitis exacerbates cardiac problems, as shown in both experimental studies and human subjects. Due to these factors, it is very likely that the prevention of periodontitis has an influence on the occurrence or advancement of cardiovascular disease (CVD) and diabetes. In this review, we have presented an updated report on the current understanding of periodontal disease and its negative impact on cardiovascular health and diabetes. We have included information on the latest preclinical research and epidemiological findings. Keywords: periodontitis, inflammation, bacteria, cardiovascular disease, diabetes.